Taking it to the extreme: prevalence and nature of extremist sentiment in games - Kowert, Rachel; Kilmer, Elizabeth; Newhouse, Alex (Frontiers in Psychology, 2024)
More than half of all game players report experiencing some form of hate, harassment or abuse within gaming spaces. While prevalence assessments of these actions in digital gaming spaces are ongoing, little remains known about the more extreme forms of these behaviors. Specifically, experiences of extremism. This paper addresses the gap in research knowledge around the expression of extremist sentiment in games by evaluating their prevalence, location, and nature, and impact. Assessing experiences via an online survey, game players (n = 423) reported an alarmingly high rate of frequency for being the direct target of, as well as a witness to, all forms of extremist content. Most of these experiences were text-based, reported to be happening ingame. Most players endorsed statements relating to a normalization of extreme ideologies within gaming cultures. It is promising that reporting these behaviors was the primary action taken by players for most of the players; however, "ignoring" these actions was also a common strategy. It is possible that player inaction reflects the embeddedness and normalization of these actions in gaming spaces and/or a lack of trust in moderation systems to be responsive. The prevalence of extreme sentiment in gaming cultures should raise concern from game makers, members of the gaming community, parents, and policy makers alike.